FINANCIAL SUSTAINABILITY MODELS IN ISLAMIC SCHOOLS: A STUDY AT SD PLUS INTAN AL-SALI BANDUNG - Putri, Silviana; Nurhasanah, Siti; Zakiyah, Sarah; Fadlla Ilahiya, Nabila; Hidayat, Ara (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
This study is motivated by the urgency to strengthen the financial sustainability of Islamic educational institutions amid the dynamic changes in funding environments and the growing operational demands of schools. The main issue examined is the dependence of SD Plus Intan Al-Sali Bandung on fluctuating funding sources, particularly community donations and foundation subsidies, which may create long-term financial instability. The purpose of this study is to formulate a relevant, measurable, and implementable financial sustainability model for Islamic-based schools by considering the characteristics of philanthropy, governance, and educational management. This research employs a qualitative approach using data collection techniques comprising in-depth interviews, direct observations, and document analysis, which are then examined through thematic analysis to identify funding patterns, financial governance effectiveness, and institutional risks. The findings reveal that the school’s funding structure, which consists of parental contributions, BOS funds, RMP assistance, foundation subsidies, and community donations, has not yet ensured long-term stability due to insufficient income diversification and limited school autonomy in budget decision-making. The analysis also shows that the absence of productive business units and the continued reliance on manual financial administration constitute significant barriers to strengthening governance. This study concludes that a hybrid funding model integrating Islamic philanthropy with educational entrepreneurship is a strategic approach to enhancing the school’s financial resilience. The study further recommends the need for comparative research across various Islamic educational institutions and an in-depth exploration of financial digitalization as a modern instrument for strengthening institutional independence.